Analysis of certificate of entitlement bidding system in Singapore - Chua, Wei Feng (2019)
Auctions are one of the important mechanisms in which optimal allocation to individuals can be achieved. In this paper, the COE bidding system was analyzed under the Independent Private Value model and thereafter categorized as a multiunit English auction. Comparisons between Singapore’s COE bidding system and the vehicle license allocation system found in Shanghai, Beijing and Guangzhou were drawn upon and studied on in various papers. In terms of revealing their true valuations, bidders in Singapore are more likely to bid their true values than bidders in Shanghai. From an efficiency perspective, the lottery system in Beijing is generally inefficient and Singapore’s COE bidding system is slightly more efficient than the hybrid system in Guangzhou. A study by Zhou, Qi, Wang (2017) demonstrated the possibility of balancing efficiency and equality adopting a new mechanism. Therefore, we proposed a new auction format in which bidders with a monthly household income of less than $10000 were classified as priority group and the rest of the bidders were classified as normal group with 2 separate auctions being conducted in each group. To determine the efficiency and equality of this new auction format, a simulation was conducted, and observations suggest the possibility of increasing equality by randomizing the number of licenses allocated to the priority group using a Uniform, Normal and Exponential distributions in the range of [ /4,1] where represents the quota for the entire auction. However, this comes at the expense of a reduced efficiency of the auction.